PENERAPAN BLENDED-PROBLEM BASED LEARNING DI MASA PANDEMI UNTUK MENINGKATKAN CRITICAL THINKING MAHASISWA PENDIDIKAN GURU SEKOLAH DASAR - Putera, Rafhi Febryan; Mahfuzah, Ainun; S, Farida; Habibi, M.; Iskandar, Puguh (Jurnal Ilmiah Aquinas, 2021)
The Covid pandemic requires blended learning (a combination of face-to-face and online learning). The low ability to think critically in class makes the learning process not optimal, therefore it is necessary to increase students' critical thinking skills using the Blended-Problem Based Learning learning model. The method used is classroom action research with a sample of 73 semester VI students in the learning media course for Primary School Teacher Education at Padang State University. Students 'initial critical thinking ability was in the very poor category with a percentage of 41%, after the first cycle there was an increase in students' critical thinking skills by 15% and cycle II by 27%. It can be concluded that the Blended-Problem Based Learning learning model can improve students' critical thinking skills